Socio-Economic Determinants that Hinder the Women from Getting Benefit Under National Health Mission - Sachin and Dr Santosh Nandal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The National Health Mission (NHM) in India was launched to improve access to healthcare, with a focus on maternal and child health, among other vulnerable groups. However, despite significant progress, women, especially in rural and marginalized communities, continue to face socio-economic barriers that hinder their full participation in and benefit from the mission's programs. This paper explores the socio-economic determinants—such as poverty, cultural norms, gender inequality, lack of education, geographic location, and health system challenges—that prevent women from accessing the healthcare services and benefits provided under NHM. The paper also highlights the need for policy reforms, targeted interventions, and a multi-pronged approach to ensure equitable healthcare access for all women.